2005
DOI: 10.1186/1471-2458-5-135
|View full text |Cite
|
Sign up to set email alerts
|

Use of a food frequency questionnaire in American Indian and Caucasian pregnant women: a validation study

Abstract: BackgroundFood frequency questionnaires (FFQs) have been validated in pregnant women, but few studies have focused specifically on low-income women and minorities. The purpose of this study was to examine the validity of the Harvard Service FFQ (HSFFQ) among low-income American Indian and Caucasian pregnant women.MethodsThe 100-item HSFFQ was administered three times to a sample of pregnant women, and two sets of 24-hour recalls (six total) were collected at approximately 12 and 28 weeks of gestation. The samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(63 citation statements)
references
References 36 publications
8
54
1
Order By: Relevance
“…In a metaanalysis of 23 trials assessing dietary intake at multiple time points, a small increase of w140 kJ/d was reported, although mean energy intake was below the respective national recommendations (1). Interestingly, some of the included studies reported decreases in energy intake, although the magnitude was small and statistically nonsignificant, similar to the present study (29)(30)(31)(32)(33). Increasing BMI and sedentariness in the background population may also contribute to altered energy expenditure patterns in pregnancy.…”
Section: Starch Intakesupporting
confidence: 45%
“…In a metaanalysis of 23 trials assessing dietary intake at multiple time points, a small increase of w140 kJ/d was reported, although mean energy intake was below the respective national recommendations (1). Interestingly, some of the included studies reported decreases in energy intake, although the magnitude was small and statistically nonsignificant, similar to the present study (29)(30)(31)(32)(33). Increasing BMI and sedentariness in the background population may also contribute to altered energy expenditure patterns in pregnancy.…”
Section: Starch Intakesupporting
confidence: 45%
“…In a study conducted among pregnant women in Brazil, Giacomello et al (14) identified Pearson's correlation coefficients of between 0?01 for saturated fats and 0?47 for Ca, taking two 48hR as the reference method. The low correlation coefficients seen in validation studies of FFQ for pregnant women can be partially explained by the high within-person variability in estimated energy and nutrient intakes during this phase of life, especially when few replications of 24hR or records are taken as the reference method (12) .…”
Section: Discussionmentioning
confidence: 99%
“…We measured minutes of driving time from patient home to 1) primary-care clinic and 2) the central hospital, where the endoscopy facility is located because increased travel time may be associated with lower CRC test use. (22) Driving time was calculated with MapQuest’s Open Document API Web Service which uses OpenStreetMap (OSM) data. OSM is a collaborative open-source participatory GIS map updated weekly with data provided by various, registered contributors, including international government agencies.…”
Section: Methodsmentioning
confidence: 99%